Arabidopsis VILLIN5, an Actin Filament Bundling and Severing Protein, Is Necessary for Normal Pollen Tube Growth([W]) - Zhang, Hua (American Society of Plant Biologists, 2010)
A dynamic actin cytoskeleton is essential for pollen germination and tube growth. However, the molecular mechanisms underlying the organization and turnover of the actin cytoskeleton in pollen remain poorly understood. Villin plays a key role in the formation of higher-order structures from actin filaments and in the regulation of actin dynamics in eukaryotic cells. It belongs to the villin/gelsolin/fragmin superfamily of actin binding proteins and is composed of six gelsolin-homology domains at its core and a villin headpiece domain at its C terminus. Recently, several villin family members from plants have been shown to sever, cap, and bundle actin filaments in vitro. Here, we characterized a villin isovariant, Arabidopsis thaliana VILLIN5 (VLN5), that is highly and preferentially expressed in pollen. VLN5 loss-of-function retarded pollen tube growth and sensitized actin filaments in pollen grains and tubes to latrunculin B. In vitro biochemical analyses revealed that VLN5 is a typical member of the villin family and retains a full suite of activities, including barbed-end capping, filament bundling, and calcium-dependent severing. The severing activity was confirmed with time-lapse evanescent wave microscopy of individual actin filaments in vitro. We propose that VLN5 is a major regulator of actin filament stability and turnover that functions in concert with oscillatory calcium gradients in pollen and therefore plays an integral role in pollen germination and tube growth.